Adnexal tumors in children clinically mimicking basal cell carcinoma. - Puente-Pablo, N.; Tardío, J.C.; Nájera, L.; Hernández-Núñez, A.; Freites-Martínez, A.; Borbujo, J.M. (European Journal of Pediatric Dermatology, 2015)
Trichoblastoma and trichofolliculoma are unusual adnexal tumors in the pediatric population. As clinical presentation is unspecific, misdiagnosed cases as basal or squamous cell carcinoma are described. Besides, histological differentiation between basal cell carcinoma and trichoblastoma is also difficult. As long as trichoblastoma and trichofolliculoma are benign tumours, treatment is optional. However, complete excision of trichoblastoma is often advised since it can continue growing. Relapse or malignant transformation of solitary lesions is unusual. Here are reported two pediatric cases of typically adult follicular tumors.